A Review on Biomarkers for the Evaluation of Autoimmune Cholestatic Liver Diseases and Their Overlap Syndromes - Nguyen, Henry H.; Fritzler, Marvin J.; Swain, Mark G. (Frontiers in Molecular Medicine, 2022)
Autoimmune cholestatic liver disease includes both Primary Biliary Cholangitis (PBC) and Primary Sclerosing Cholangitis (PSC). Both conditions result in impairment of hepatic bile flow ultimately leading to chronic liver injury, liver fibrosis and eventually end stage cirrhosis. Early and accurate diagnosis are important for the risk stratification, follow up and management of these patients. The underlying pathogenesis of these conditions have not been completely resolved and poses a barrier for the development of new diagnostic and prognostics tools. Current research work suggests that the pathogenesis of autoimmune cholestatic liver disease results from environmental, genetic, and a large component of underlying immune dysfunction. While the current available serum biomarkers and imaging modalities showcases progression in precision medicine for the management of autoimmune cholestatic liver disease, development of new biomarkers are still an area of need in this field. In this review, we will discuss the current and emerging biomarkers in patients with PBC, PSC, and a special population that exhibit overlap syndrome with autoimmune hepatitis (AIH). The use of these biomarkers for diagnosis and prognosis of these patients will be reviewed through the lens of the current understanding of the complex immune pathophysiology of these conditions.